Macroeconomic Dynamics Toward International Aviation Demand in Indonesia - Robi Saputra; Dwita Sakuntala; Suhendi Suhendi (Journal of Research in Social Science and Humanities, 2025)
The international aviation sector plays a strategic role in supporting global mobility and Indonesia's economic recovery, particularly in the post-COVID-19 pandemic period. This study aims to analyze the influence of macroeconomic variables on international aviation demand in Indonesia from 2010 to 2024. The variables examined include economic growth, exchange rates, airfares, visa fees, and world oil prices, with the number of international passengers serving as the primary indicator of aviation demand. The research findings indicate a long-term relationship between macroeconomic variables and international aviation demand. Exchange rates and the number of international passengers have a positive and significant impact on demand, while economic growth and visa fees show a significant negative influence. In the short term, the dynamics of international aviation demand are influenced by passenger movement patterns from the previous period, with a rapid and stable adjustment process toward equilibrium.